Perceptual learning - Fahle, Manfred; Poggio, Tomaso (Bradford Bks., 2002)
Perceptual learning is the specific and relatively permanent modification of perception and behavior following sensory experience. It encompasses parts of the learning process that are independent from conscious forms of learning and involve structural and/or functional changes in primary sensory cortices. A familiar example is the treatment for a "lazy" or crossed eye. Covering the good eye causes gradual improvement in the weaker eye's cortical representations. If the good eye is patched too long, however, it learns to see less acutely. This book presents advances made in the last decade in this rapidly growing field. The first part examines neuronal changes caused by lesions or external influences. It discusses the effects of these changes on behavior and the extent to which plasticity in sensory systems is possible. Taking a broader view, the second part looks at how more conscious or systemic stimuli cause cortical changes. Clinical trials in which subjects are taught to recognize visual and auditory stimuli demonstrate the relationship between perceptual and cognitive learning. The final sections offer general models of perceptual learning and discuss the future of the field.